TISSUE REGENERATION PROCEDURES FOR ALVEOLAR PRESERVATION: A SYSTEMATIC REVIEW (CIPEEX, 2024)
After tooth extraction, a physiological process of alveolar bone resorption begins. Thesurrounding soft tissues also undergo changes. The replacement of the lost tooth bymeans of implants can be difficult or even prevented by the lack of hard tissue foranchoring and stability of the implant. The lack of soft tissue impairs the aestheticresult and longevity of the work due to loss of protection of the implant/prosthetic parttransition zone. For these reasons, research seeks to investigate the use ofallogeneic and/or xenogeneic materials to preserve bone structure after toothextraction through selective repopulation of cells and tissues. The objective of thisstudy was to systematically review the literature in search of randomized clinical trialscarried out in humans who underwent tooth extraction associated or not with tissueregeneration for alveolar preservation with a view to rehabilitation withosseointegrated implants. The scientific literature was surveyed and 597 studieswere found in Pubmed, Web of Science, Embase, Scopus, Cochrane and Lilacs/BBOdatabases. After removal of duplicates, analysis process and final selection ofstudies, 10 randomized controlled trials were included in the qualitative analysis. Theresults indicate that sockets treated with bone graft with allogeneic/xenogeneicmaterial present greater reduction of the bone defect after extraction than sockets inspontaneous healing. This review encourages the performance of alveolarregeneration procedures to optimize rehabilitation through dental implants. Theprotocol of this systematic review was registered in PROSPERO (CRD42021248413)and followed the PRISMA recommendation rules (Key Items for ReportingSystematic Reviews and Meta-analyses).
Keywords: Systematic Review; Bone Transplantation; Tooth Extraction; Bone Regeneration; Guided Tissue Regeneration.